Penerapan Model Pembelajaran Discovery Learning Berbantuan Media Interaktif untuk Meningkatkan Hasil Belajar Peserta Didik di SDN 1 Kebonadem Kabupaten Kendal - Naila Nur Anisa; Ika Septiana; Elis Dwi Purbiyanti (Universitas Pendidikan Mandalika, 2021)
The purpose of this study is to apply a discovery learning model assisted by interactive media to improve the learning outcomes of fifth grade students at SDN 1 Kebonadem in the 2020/2021 academic year. This research method uses classroom action research. The subjects of this study were the fifth grade students, totaling 25 students. This research instrument uses observation, tests, and documentation. While the data analysis technique used descriptive analysis. The results of this study indicate that there is an increase in learning outcomes for Theme 9 by using a discovery learning model assisted by interactive media for the fifth grade students of SDN 1 Kebonadem. This can be seen from the increase in the average student learning outcomes from the initial condition which was only 61 with 16% complete learning outcomes, an increase in the first cycle of 69 with 60% learning outcomes, increasing again in the second cycle with average learning outcomes. by 72 with 72% completeness learning outcomes and in the third cycle the average student learning outcomes increased again by 82 with 88% complete learning outcomes. So that the performance indicator, namely complete learning can be achieved.